Preparation of gastrodin‐modified dendrimer‐entrapped gold nanoparticles as a drug delivery system for cerebral ischemia–reperfusion injury. Issue 12 (21st November 2022) - Huang, Wenqiang; Wang, Lanlin; Zou, Yanghong; Ding, Xiangqian; Geng, Xin; Li, Jinghui; Zhao, Hexiang; Qi, Renli; Li, Shipeng
Abstract: Objective: This study sought to evaluate the feasibility of multifunctional gastrodin (GAS)‐containing nano‐drug carrier system against cerebral ischemia–reperfusion injury (CIRI). Methods: The drug‐loaded nanocomposite (Au‐G5.NHAc‐PS/GAS) with certain encapsulation efficiency (EE) was prepared by physical adsorption method using different proportions of GAS and drug‐carrying system (Au‐G5.NHAc‐PS). High‐performance liquid chromatography was used to determine the drug loading and EE. Cultured rat astrocytes and hypothalamic neurons were assigned into four groups: PBS, Au‐G5.NHAc‐PS, Au‐G5.NHAc‐PS/GAS, and GAS. CCK‐8 assay, flow cytometry, and quantitative real‐time PCR were performed to examine the cell viability, apoptosis, and the expression of tumor necrosis factor‐α (TNF‐α), IL‐1β, and IL‐6 in the astrocytes and hypothalamic neurons, respectively. Cellular uptake of GAS and Au‐G5.NHAc‐PS/GAS was analyzed by using Hoechst 33342 staining. The animal model with focal cerebral ischemia was generated by middle cerebral artery occlusion (MCAO) in healthy male Sprague Dawley (SD) rats, and pathological changes of brain tissue and major organs in the rats were identified by hematoxylin and eosin (HE) staining. Apoptosis in rat astrocytes and hypothalamic neurons was detected by TUNEL staining and flow cytometry. Results: Au‐G5.NHAc‐PS had a spherical shape with a uniform size of 157.3 nm. Among the nanoparticles, Au‐G5.NHAc‐PS/GAS with an EE of 70.3% displayed the best release delay effect. Moreover, we observed that in vitro cytotoxicity and cellular uptake of Au‐G5.NHAc‐PS/GAS were higher than those of GAS, whereas the expression of TNF‐α, IL‐1β, and IL‐6 was significantly downregulated in Au‐G5.NHAc‐PS/GAS group as compared to G5.NHAc‐PS group. Notably, HE staining revealed that although Au‐G5.NHAc‐PS/GAS had no toxic and side effects on the main organs of rats, it alleviated the damage of brain tissue in the MCAO rats. Besides, Au‐G5.NHAc/GAS markedly reduced MCAO‐induced apoptosis. Conclusion: Au‐G5.NHAc‐PS showed favorable surface morphology, sustained drug release ability, no measurable toxicity, and good biocompatibility, indicating that GAS exerts anti‐inflammatory and antiapoptotic effects on CIRI. Abstract :